Factors Influencing Quality of Life in Patients with Myocardial Infraction - Ali Hsanpour-Dehkordi; Ali-Akbar Nazari; Mohammd-Saeed; Ahmad-Ali; Nasrin Forouzandeh; Karam-Ali Kasiri; Reza Masoudi; Ahmad Mousavi; Seyed-Masih Hosseini (Iran University of Medical Sciences, 2009)
Background & Aim : Myocardial infarction is a common and dangerous life threatening disease with an impact on quality of life. The present descriptive-analytical study aims to determine quality of life in patients with myocardial infarction referring to Hadjar hospital affiliated to the Shahre-kord University of Medical Sciences.   Material & Method : This was a descriptive-analytical study in which 150 patients admitted to cardiac care unit of Hadja hospital within 8 weeks post infarction were selected by non random sampling method. Data were collected through interview, patients' medical records and patients self report. The tool for collecting data regarding quality of life was SF36 questionnaire. Data were analyzed by descriptive and inferential statistics.   Results: Findings showed that the mean value of age was 55.7 ±10.5 and that quality of life in majority of subjects (%53) was fairly favorable. Regarding aspects of quality of life, most patients had fairly favorable general status (physical and psychological health) (%62) and social function (%65). Also, sleep pattern of majority of subjects (%61) was favorable and most of them (62%) had unfavorable physical activity. There was statistically significant correlation between quality of life and variables such as duration of disease (P<0.05), intensity of pain (P<0.05), decline or loss of job function, and the degree of fatigue (P<0.05), but there was no statistically significant relationship between quality of life and other demographics as age, gender, marital status, economic status and occupational status.   Conclusion: Because fatigue and pain have some relationship with quality of life in patient with myocardial infarction, health care personnel, spatially nurses should pay attention to dimensions of quality of life when planning care for these patients. Failure to do so may leads to quality of life of patients to be neglected.